2010
DOI: 10.1089/bsp.2009.0061
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Paramedic Response Readiness for CBRNE Threats

Abstract: Paramedics play a pivotal role in the response to major emergencies. Recent evidence indicates that their confidence and willingness to respond to chemical, biological, radiological, nuclear, and explosives-related (CBRNE) incidents differs from that relating to their ''routine'' emergency work. To further investigate the factors underpinning their readiness to respond to CBRNE incidents, paramedics in New South Wales (NSW), Australia, were asked to complete a validated online survey instrument. Univariate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 17 publications
0
37
1
Order By: Relevance
“…Another study among Australian paramedics in New South Wales found that training increases perception of CBRN readiness by 25%. Paramedics with previous experience were more likely to report readiness than inexperienced personnel . Interestingly, the study found that the benefit of having previous experience disappeared when controlling for training as a confounder .…”
Section: Discussionmentioning
confidence: 77%
“…Another study among Australian paramedics in New South Wales found that training increases perception of CBRN readiness by 25%. Paramedics with previous experience were more likely to report readiness than inexperienced personnel . Interestingly, the study found that the benefit of having previous experience disappeared when controlling for training as a confounder .…”
Section: Discussionmentioning
confidence: 77%
“…Practical training is a strong factor for preparedness and it is stated [11] that the participants who had experience from real CBRNE events, experienced no significant higher readiness than those who performed a CBRNE exercise. A study on the correlation between the number of hours of training between paramedics and fire personnel practicing for major incidents and disasters and the perceived preparedness for these events showed that the level of perceived preparedness increased with the number of hours practiced [12].…”
Section: Discussionmentioning
confidence: 99%
“…It was found in another study that practical exercise compared to real events attained a more lasting knowledge of the performance of triage, which also enhances the idea of supplementing theoretical training with practical exercises. Practical exercises allow for feedback and the correction of errors in a safe learning environment, compared to actual events [11].…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy-focused education for these workers may constitute cognitive ‘interventions’ that promote lower concern and greater response willingness; outcomes that may be crucial in maintaining emergency ‘surge’ capacity [17]. Among Australian paramedics for example, receipt of terrorism-related training focused on key competencies was found to be a stronger predictor of response readiness than career incident experience [36]. …”
Section: Discussionmentioning
confidence: 99%